Managers and efficiency in banking - Karlo Kauko (Bank of Finland, 2007)
This paper presents evidence on the impact of managers on cost efficiency in banking. Stochastic frontier analysis is applied to a unique Finnish data set. The paper finds that manager age and education have strong yet complicated effects. University education enhances efficiency if the manager is running a large bank. Managing director changes are systematically followed by efficiency changes. Manager retirement typically causes an efficiency improvement, whereas other manager changes can either improve or weaken efficiency.
URN:NBN:fi:bof-20140807445
Keywords: G21; L25; M19; 330; efficiency; banking; managers